Seizure outcomes after meningioma resection - Mehar Masroor; Saqib Kamran Bakhshi; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2022)
Meningiomas are one of the most common primary brain tumours, and seizures are a common presenting symptom. Complete tumour resection results in seizure freedom in up to 90% patients. The use of AEDs in these patients is inconsistent, and current evidence shows that they do not have any benefit in long-term seizure prevention after resection. Tumour histology, location, surrounding oedema, recurrence and post-operative complications are important risk factors for having post-operative seizures. Keywords: Brain tumour, Meningioma, Seizure, Anti-epileptic drugs. Continue...